The long wait - Legaspi, Corsie; Lazaro, Cheche (The Probe Team ; [episode no. 169], 1991)
The topics dealth with are: the Filipino war veterans of WW II waiting for war benefits from U. S. ; Fr. Corsie Legaspi using divine healing; and a tennis competition against Sweden led by Felix Barrientos.